1998
DOI: 10.1074/jbc.273.50.33174
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor Desensitization in NG108-15 Cells

Abstract: In NG108-15 cells inhibition of both N-type calcium channel current and adenylyl cyclase by somatostatin (SRIF) was not sustained but rapidly desensitized in the continued presence of the drug. The degree and rate of desensitization were concentration-dependent, and the desensitization was homologous with respect to the ␦-opioid receptor. We have been unable to obtain evidence for the involvement of G protein-coupled receptor kinases (GRKs) in this desensitization. SRIF-induced desensitization of N-type calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 69 publications
5
58
1
Order By: Relevance
“…The present study demonstrated a decline in CRF 1 binding capacity in neocortex, associated with increased CRF 1 mRNA expression. These findings are consistent with a mechanism of transient receptor elimination due to internalization, which leads to enhanced receptor mRNA transcription as has been shown in several other G-protein-coupled receptor systems (8,29,52). In other systems, this ligandinduced receptor internalization has been proposed to contribute to receptor desensitization via cell surface receptor downregulation (8,29), as well as by regulating transcription of mRNA (52).…”
Section: Discussionsupporting
confidence: 78%
“…The present study demonstrated a decline in CRF 1 binding capacity in neocortex, associated with increased CRF 1 mRNA expression. These findings are consistent with a mechanism of transient receptor elimination due to internalization, which leads to enhanced receptor mRNA transcription as has been shown in several other G-protein-coupled receptor systems (8,29,52). In other systems, this ligandinduced receptor internalization has been proposed to contribute to receptor desensitization via cell surface receptor downregulation (8,29), as well as by regulating transcription of mRNA (52).…”
Section: Discussionsupporting
confidence: 78%
“…3). PAO, a tri-arsenical compound, blocks endocytosis of macromolecules by cross-linking proteins with sulfur groups and inhibits internalization of various kinds of membrane receptors (34,37,38), including PAF receptor (20,21). ConA or hypertonic sucrose also inhibits the internalization of many receptors including PAF receptor (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, agonist stimulation of GTPγS binding reflects receptor activation of all receptor-interacting G proteins, including the pertussis toxin sensitive G proteins that couple somatostatin receptors to adenylyl cyclase and the pertussis toxin insensitive G proteins that are at least partially responsible for coupling receptors to phospholipase C. Further, since cyclic AMP measurements were made after 15 min of agonist stimulation whereas phosphoinositide production was determined after 50 min of stimulation, the effect of receptor desensitization will differ in the two assays. We now know that desensitization can occur after few minutes of agonist stimulation for several somatostatin receptor subtypes (Beaumont et al, 1998;Elberg et al, 2002;Engstrom et al, 2006;Hipkin et al, 1997;Holliday et al, 2007;Liu et al, 2000). Thus, desensitization will influence second messenger formation in assays conducted in intact cells and the impact of desensitization on such measurements will vary with the time of incubation.…”
Section: Functionally Selective Agonists At Somatostatin Receptorsmentioning
confidence: 99%